The Impact of Formative Assessment Towards Students’ Motivation in Learning English: A Meta Analysis - Sunra, La; Samtidar, Samtidar (Tamaddun Life, 2023)
This meta-analysis explores the impact of formative assessment on students' motivation in learning English as a foreign language (EFL) within the context of Indonesia. Drawing on a comprehensive search and analysis of relevant literature, the review investigates the impact of formative assessment on intrinsic and extrinsic motivation, and proposes strategies to enhance motivation through formative assessment. This review examined 37 qualifying studies and analyzes the formative assessment impact, which have been categorized into three aspects namely; (1) the impact on intrinsic motivation, (2) the impact on extrinsic motivation, and (3) the impact on academic motivation and the potential strategies which consisted of four aspects such as (1) Promote Collaboration and Group Work, (2) Scaffold Learning and Provide Support, (3) Encourage Reflective Practices, and (4) Foster a Sense of Competence and Progress. The implications for practice highlight practical recommendations for educators to implement formative assessment strategies in the Indonesian EFL context. By integrating these recommendations, educators can create a dynamic learning environment that enhances students' motivation, engagement, and overall language learning success.